Participation in public and social media interactions - Dynel, Marta; Chovanec, Jan (Pragmatics & beyond, 2015)
"This chapter discusses the function of blogs as tools enhancing citizen participation in political communication. Adopting the perspective of corpus-assisted critical discourse analysis, a set of blogs from the US presidential election campaign are analysed in order to determine the frequency of reference to the candidates, the parties, as well as the bloggers themselves. The analysis of pronoun choice, verbs and modality indicate that blogs enhance participation rhetoric. The data further indicate that citizen bloggers attach more importance to individual political figures than party bloggers do. The tendency to refer to the candidates rather than to their political affiliation may be explained as evidence that people not belonging to parties interpret politics as a struggle between different politicians and not between different ideologies. Since the language representation of the political scene in citizens' blogs shows distinct traces of the ongoing process of personalization of politics, the political blog can be considered as a 'tool of citizen empowerment'"--Provided by publisher